Determination of procalcitonin content in blood serum, urine, and ejaculate for the diagnosis of urogenital tract pathology - D. Yu. Sosnin; K. R. Gal’kovich (Сибирский научный медицинский журнал)
The determination of the concentration of procalcitonin (PCT) in blood serum and other biological fluids is used for the diagnosis and monitoring of the course of sepsis and the syndrome of a systemic inflammatory reaction. This review summarizes the data on the diagnostic value of the definition of procalcitonin in the practice of urologists and andrologists. The content of procalcitonin in such biological fluids as urine, seminal plasma is almost 10 times higher than the level of this protein in blood serum: this phenomenon is manifested in physiological conditions and in pathological processes. The relationship of clinical and laboratory indicators of inflammation with the severity of urosepsis was analyzed. Elevated serum procalcitonin levels are considered as a predictor of septic shock in patients with urolithiasis, and determine the management tactics of patients with urinary tract obstruction. The marker function of this protein was studied in inflammation in the renal parenchyma, in malignant neoplasms of the kidneys, bladder, ureter, prostate and testis; in the diagnosis of testicular torsion and orchiepididymitis. The article describes the regular changes in the level of urinary procalcitonin depending on the severity of vesicoureteral reflux, the severity of the manifestations of the inflammatory reaction. There were significant differences in the concentration of procalcitonin in seminal plasma between the groups of men with reduced and normal ejaculate fertility.